2009
DOI: 10.1021/jp811130k
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Dissociation of CO on Body-Centered Cubic Transition Metals and Alloys: Effect of Coverage and Scaling Relations

Abstract: The adsorption and dissociation of CO have been calculated on the (100) surfaces of the body-centered cubic transition metals Fe, Mo, Cr, and W and the alloys Fe3Mo and Fe3Cr using density functional theory for two CO coverages, 0.25 and 0.5 ML. A complete analysis of the vibrational frequencies was performed to check whether the calculated structures are stable geometries or transition-state structures. For coverages up to 0.25 ML, carbon monoxide adsorbs molecularly onto all four metals at fourfold hollow si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 76 publications
5
20
0
Order By: Relevance
“…11 Chemisorption and dissociation of CO on Fe(100) has been studied extensively using density functional theory (DFT) which has confirmed tilted CO at the four-fold hollow site as the most strongly bound and has provided reliable estimates of barriers to diffusion and dissociation. [13][14][15][16][17][18][19][20][21][22] In the present work we extend the analysis by combining experimental measurement of the atom-projected 2p density of states using x-ray emission spectroscopy (XES) with DFT calculations of spectra and bonding. XES is a corelevel spectroscopy measuring the photon emitted when a valence electron decays to fill a previously created core-hole in a non-Auger process.…”
Section: Introductionmentioning
confidence: 96%
“…11 Chemisorption and dissociation of CO on Fe(100) has been studied extensively using density functional theory (DFT) which has confirmed tilted CO at the four-fold hollow site as the most strongly bound and has provided reliable estimates of barriers to diffusion and dissociation. [13][14][15][16][17][18][19][20][21][22] In the present work we extend the analysis by combining experimental measurement of the atom-projected 2p density of states using x-ray emission spectroscopy (XES) with DFT calculations of spectra and bonding. XES is a corelevel spectroscopy measuring the photon emitted when a valence electron decays to fill a previously created core-hole in a non-Auger process.…”
Section: Introductionmentioning
confidence: 96%
“…The latter converts the catalyst into iron carbides. Among the mixture of carbide and oxide phases [5][6][7][8] present under process conditions, the Hägg carbide (v-Fe 5 C 2 ) is generally regarded as the active phase for FTS [2,5,6,[9][10][11][12][13][14][15][16][17][18], although other phases such as e-Fe 2.2 C or h-Fe 3 C may exhibit activity as well [9]. Mechanistic studies on CO hydrogenation and FTS on metallic iron surfaces are available in the literature [4,14,[19][20][21][22][23][24][25][26][27][28][29], but studies on the catalytic properties of iron carbides in FTS are scarce, we refer to de Smit and Weckhuysen [13] for a recent review and to other literature [3,5,[8][9][10][11]13,15,24,[30][31][32][33][34][35]…”
Section: Introductionmentioning
confidence: 99%
“…The overall energy balance is À0.93 eV in agreement with previous work. [7,9] The activation energy for the direct process is 1.09 eV, which is smaller than the CO dissociation barrier when no hydrogen is present (1.2 eV), showing that the H-atom affects the TS more than the IS. On the other hand, Scheijen et al [7] have found an increase of 0.05 eV in the barrier for CO dissociation when its coverage increased from 0.25 to 0.5 on Fe (100).…”
mentioning
confidence: 95%
“…[1,2] Many recent computational studies have addressed the mechanism for this reaction. [3][4][5][6][7] Dissociation of the CO bond is a key step in the initiation of the F-T process. In principle it may occur through one of three pathways: [8] a) CO ads + * !C ads + O ads b) CO ads + H ads $HCO ads + * !HC ads + O ads c) CO ads + Hads$COH ads + * !C ads + OH ads where * stands for the active site.…”
mentioning
confidence: 99%
See 1 more Smart Citation